2017
DOI: 10.24099/vet.arhiv.160727
|View full text |Cite
|
Sign up to set email alerts
|

Virulence gene profiles of Pasteurella multocida strains isolated from cattle and buffalo

Abstract: Pasteurella multocida is responsible for numerous economically relevant diseases in domestic animals worldwide. In cattle and buffaloes the organism is associated with hemorrhagic septicemia (hS) and bovine respiratory disease (BrD). the aim of this study was to investigate twelve virulence associated genes in 22 strains of P. multocida isolated from slaughtered cattle and buffaloes. the most frequently detected genes among bovine isolates were ptfA, nanH, exbBD-tonB and oma87; whereas hgbB and toxA genes occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…The frequency of this gene among different hosts, irrespective of their origin, has been reported from 84.6% to 100%, while it was present in 73.9% of Brazilian rabbit isolates (2,5,6,7,17,19,20). In addition, a previous study on Iranian cattle and buffalo isolates indicated the presence of hgbA gene among 77.2% of all studied isolates (10).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The frequency of this gene among different hosts, irrespective of their origin, has been reported from 84.6% to 100%, while it was present in 73.9% of Brazilian rabbit isolates (2,5,6,7,17,19,20). In addition, a previous study on Iranian cattle and buffalo isolates indicated the presence of hgbA gene among 77.2% of all studied isolates (10).…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, it has been demonstrated that 100% of Iranian and Indian cattle isolates possessed this gene, while some other studies indicated the presence of this gene in 57.4, 57.7, and 61.3% of ovine and cattle isolates from Iran, Germany, and Japan, respectively (2,5,9,(17)(18)(19)(20). In contrast, it has been reported that only 40.9% of Iranian cattle and buffalo isolates from Khuzestan possessed this gene (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations